2013
DOI: 10.3844/ajebasp.2013.22.28
|View full text |Cite
|
Sign up to set email alerts
|

Single-Digit Inflation Targeting and Economic Growth

Abstract: In recent times, most central banks have adopted inflation-targeting monetary policy approach aimed primarily to achieve single-digit inflation. Though, the literature suggest that low level of inflation promotes economic growth, the literature is silent on the threshold inflation level needed to promote growth. Studies in developing countries that seek to estimate the threshold level of inflation that promotes economic growth do not support single-digit inflation level. The question that arises is whether sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…The findings in the short run means that inflation targeting does not play any instrumental role in promoting economic growth in the short run. The findings in the short run of the study are contrary to that of Ayisi [40] who found a positive significant relationship between inflation targeting and gross domestic product growth in the short run in Ghana. The extent of the contradiction in results could be as a result of the span of the data.…”
Section: Short Run Dynamic Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The findings in the short run means that inflation targeting does not play any instrumental role in promoting economic growth in the short run. The findings in the short run of the study are contrary to that of Ayisi [40] who found a positive significant relationship between inflation targeting and gross domestic product growth in the short run in Ghana. The extent of the contradiction in results could be as a result of the span of the data.…”
Section: Short Run Dynamic Resultscontrasting
confidence: 99%
“…This will promote general consumption of goods and services or improvement in savings and investment which are key factors in economic growth. The findings of study are consistent with Ayisi [40] who found a positive significant relationship between inflation targeting and gross domestic product growth in Ghana. The extent of the consistency in results could be as a result of the adoption of the same estimation technique.…”
Section: The Long Run Effect Of Inflation Targeting and Inflation Vol...supporting
confidence: 90%
See 1 more Smart Citation
“…The explanatory variables used as growth determinants in this research has also been used in some influential empirical works investigating the relationship between inflation and growth (Sarel, 1996;Khan and Senhadji, 2001;and Kremer, Bick and Nautz, 2009) as well as in recent works on developing economies (Risso and Carrera, 2009;Frimpong and Oten-Abayie, 2010;Seleteng, Bittencourt and van Eyden, 2011;Ghazouani, 2012;Ayisi, 2013;Ahortor, Adenekan and Ohemeng, 2012).…”
Section: Methodology and Datamentioning
confidence: 99%